Error detection and comparison of gesture control technologies - Aditya Prasad Mahapatra; Bishweashwar Sukla; Harikrishnan K. M.; Debani Prasad Mishra; Surender Reddy Salkuti (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
This paper showcases the study and observation on the error occurrence in gesture control technologies. An arduino-based gesture control environment has been developed by using the arduino board to use motion gestures to control the contents on the screen. This environment is made using position sensitive diodes as sensing devices, arduino as a micro-controller and Python to execute commands in the system. It is performed on 2 different software applications namely Google Chrome and VideoLAN Client Media Player. In Google Chrome gestures are used to traverse between tabs and also move up and down within a web page, whereas in VideoLAN Client Media Player gestures are used to control the volume and speed. Through this, the difference between two technologies i.e., infrared and ultrasonic are worked and compared. Various data visualization cues are prepared to better understand the error and the factors causing it. Thorough investigation of factors affecting the error has been done using our observation. The future of this technology and its limitations have been also discussed.